Interactive Musical Partner: A Demonstration of Musical Personality Settings for Influencing the Behavior of an Interactive Musical Generation System - Albert, Jeffrey (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2013)
The Interactive Musical Partner (IMP) is software designed for use in duo improvisations, with one human improviser and one instance of IMP, focusing on a freely improvised duo aesthetic. IMP has Musical Personality Settings (MPS) that can be set prior to performance, and these MPS guide the way IMP responds to musical input. The MPS also govern the probability of particular outcomes from IMP's creative algorithms. The IMP uses audio data feature extraction methods to listen to the human partner, and react to, or ignore, the human‚Äôs musical input, based on the current MPS. This demonstration shows how the MPS interface with IMP's generative algorithm.